Avaliação da influência dos macronutrientes na bioacumulação do chumbo pela Eichhornia crassipes - Oliveira, Ana Paula de (2012)
The main objective of this study was to verify the influence of the macronutrient phosphorus in the lead bioaccumulation process, using the living aquatic macrophyte Eicchornia crassipes. In addition, the removal capacity of lead ions and some nutrients such as P, K, Ca and Fe, by the E. crassipes was verified, obtaining also information on how these are distributed within two compartiments of the plant: roots and leaves. For this, a set of metal removal/bioaccumulation experiments, in batch mode, was performed for different concentration ranges of metal and nutrients in hydroponic conditions. Several 5 L growing solutions based on the set of macro and micronutrients specified by Clark as being adequate to cultivate plants in hydroponic conditions were prepared, containing a mixture of lead (0, 5, 10, 15 and 20 mg L-1) and phosphorus (once, twice, four and eight times of 3,2 mg L-1) concentrations among other constant essential nutrient ones. At a greenhouse and using several 8 L containers approximately 80 g of living and healthy E. crassipes aquatic macrophytes were growded in each type of 5 L growing solution, restoring its former hydroponic and metal concentration condition at each two days time interval as well as monitoring the plant weight, the aqueous medium temperature and the pH values. After predefined collection time (2, 4, 8, 16 and 32 d), samples of growing solutions and plants were separated and measured some physico-chemical parameters and then stored in plastic bags for posterior analysis. Analysis of initial and residual concentrations of lead and nutrients available in the metal-doping Clark growing solutions as well as bioaccumalated metal concentrations in the dried plant samples (roots and leaves) were performed by SR-TXRF technique, except for phosphorus concentrations which were determined by a colorimetric method. According to the TXRF results, the adsorption/accumulation of lead ions in roots and leaves of the Eichhornia crassipes was slightly favoured by the presence of high phosphorus concentrations in the metal-doping Clark growing solutions. It can be noticed that the lead removal by roots is a quit process, occurring basically a high lead adsorption in the first days, whereas the lead bioaccumulation in leaves is a low process due to ocurr a low transportation rate of nutrients for aerial parts of the aquatic plant. Beside this, high lead concentrations in metal-doping Clark solutions have negatively influenced the accumulation of phosphorous in leaves as well as a low phosphorous adsorption in roots, suggesting that there is a detrimental effect on sorption and transport of phosphourous to the leaves by the presence of lead ions. On the other hand, it was observed a high systematically increasing of potassium concentration in roots whereas a reduction on potassium ones is occurring in leaves due to the presence of lead ions, suggesting that there is a migration process of potassium from leaves to roots. It could be occurring by different possible processes such as potassium complexation in roots or occupation of lead sites by potassium during the transportation of lead to aerial parts, reducing the potassium concentration in leaves. Further nutrient and metal adsorption/bioaccumulation experiments are necessary to understand better the translocation and accumulation process of nutrients such as phosphorus and potassium when lead ions are being adsorbed and transported within the internal structure of the aquatic plant.